2012
DOI: 10.1111/j.1745-4549.2011.00664.x
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF CUMINUM CYMINUM L. ESSENTIAL OIL AND LACTOBACILLUS ACIDOPHILUS (A PROBIOTIC) ON STAPHYLOCOCCUS AUREUS DURING THE MANUFACTURE, RIPENING AND STORAGE OF WHITE BRINED CHEESE

Abstract: In this study, the effect of Cuminum cyminum L. essential oil (EO) and Lactobacillus acidophilus (a probiotic) on growth of Staphylococcus aureus in white brined cheese was evaluated. The experiment included different levels of EO (0, 7.5, 15 and 30 µL/100 mL milk) and L. acidophilus (0 and 0.5%) to assess their effects on S. aureus count during the manufacture, ripening and storage of Iranian white brined cheese for up to 75 days. The significant (P < 0.05) inhibitory effects of EO (even at its lowest concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…They indicated that high susceptibility of gram‐positive bacteria and relative sensitivity of gram‐negative bacteria are due to pronounced decrement of E. coli O157:H7 and L. monocytogenes in manufactured white cheeses during 45 days of storage time (Ehsani et al., ). Furthermore, there are several previous reports about the antimicrobial effects of other EOs, including those of Ocimum gratissimum against Aspergillus flavus , Aspergillus tamarii , Fusarium poae , Fusarium verticillioides , Penicillium citrinum , and Penicillium griseofulvum (Philippe, Souaïbou, Guy, et al., ); Cinnamomum zeylanicum and O. gratissimum against Aspergillus terreus , Aspergillus ustus , Aspergillus niger , Aspergillus aculeatus , Penicillium brevicompactum , and Scopulariopsis brevicaulis (Philippe, Souaïbou, et al., ); Cuminum cyminum L. plus Lactobacillus acidophilus against S. aureus (Sadeghi, Akhondzadeh Basti, Noori, Khanjari, & Partovi, ); rosemary and Pimpinella anisum against E. coli (Ehsani & Mahmoudi, ; Ribeiro et al., ); and Mentha spicata , Mentha pulegium , Pimenta racemosa , Syzygium aromaticum , Cinnamomum verum , and Thymus vulgaris against Listeria spp. (Smith‐ Smith‐Palmer et al., ; Moosavi, Esmaeili, & Mostafavi, ; Sadeghi et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…They indicated that high susceptibility of gram‐positive bacteria and relative sensitivity of gram‐negative bacteria are due to pronounced decrement of E. coli O157:H7 and L. monocytogenes in manufactured white cheeses during 45 days of storage time (Ehsani et al., ). Furthermore, there are several previous reports about the antimicrobial effects of other EOs, including those of Ocimum gratissimum against Aspergillus flavus , Aspergillus tamarii , Fusarium poae , Fusarium verticillioides , Penicillium citrinum , and Penicillium griseofulvum (Philippe, Souaïbou, Guy, et al., ); Cinnamomum zeylanicum and O. gratissimum against Aspergillus terreus , Aspergillus ustus , Aspergillus niger , Aspergillus aculeatus , Penicillium brevicompactum , and Scopulariopsis brevicaulis (Philippe, Souaïbou, et al., ); Cuminum cyminum L. plus Lactobacillus acidophilus against S. aureus (Sadeghi, Akhondzadeh Basti, Noori, Khanjari, & Partovi, ); rosemary and Pimpinella anisum against E. coli (Ehsani & Mahmoudi, ; Ribeiro et al., ); and Mentha spicata , Mentha pulegium , Pimenta racemosa , Syzygium aromaticum , Cinnamomum verum , and Thymus vulgaris against Listeria spp. (Smith‐ Smith‐Palmer et al., ; Moosavi, Esmaeili, & Mostafavi, ; Sadeghi et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Frequently, phenolic constituents have been consistently introduced as main antibacterial components of EOs. Nevertheless, according to chemical studies, antibacterial activity of the studied PAO can be explained by the presence of various antibacterial compounds, such as anethole and terpene hydrocarbons, along with the suppressing ability of PAO to the adhesions of bacterial cells (Abdel‐Reheem & Oraby, ; Sadeghi et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Pimpinella anisum seeds were collected from Isfahan, Iran. The EO of anise seeds was obtained using water distillation according to Sadeghi, Akhondzadeh Basti, Noori, Khanjari, and Partovi (). The resulting PAO was dried over anhydrous sodium sulfate and stored at 4°C until use.…”
Section: Methodsmentioning
confidence: 99%
“…() in cheese manufactured by pediocin‐producing Lactococcus lactis , by Amer () in domiati cheese manufactured with L. acidophilus and B. lactis and by Sadeghi et al . () in white brined cheese manufactured with L. acidophilus .…”
Section: Resultsmentioning
confidence: 99%